Apalutamide for metastatic, castration‐sensitive prostate cancer in the Japanese population: A subgroup analysis of the randomized, double‐blind, placebo‐controlled phase 3 TITAN study. (8th December 2020) - Uemura, Hirotsugu; Arai, Gaku; Uemura, Hiroji; Suzuki, Hiroyoshi; Iijima, Kazuyoshi; Nishimura, Kazuo; Fujii, Koji; Hatayama, Tomoyoshi; Aoyama, Junya; Deprince, Kris; Lopez‐Gitlitz, Angela; McCarthy, Sharon; et al.
Abstract : Objective: To evaluate the efficacy and safety of apalutamide + androgen deprivation therapy versus androgen deprivation therapy alone in Japanese patients with metastatic castration‐sensitive prostate cancer from the phase 3, randomized, global TITAN study. Methods: Men with metastatic castration‐sensitive prostate cancer randomly (1:1) received 240 mg apalutamide + androgen deprivation therapy or matching placebo + androgen deprivation therapy. The primary efficacy endpoints were radiographic progression‐free survival and overall survival. Secondary efficacy endpoints were time to cytotoxic chemotherapy, pain progression, chronic opioid use, and skeletal‐related events. Safety was also assessed. Results: Of the 1052 patients included in the TITAN study, 51 (4.85%) were Japanese (apalutamide group, n  = 28; placebo group, n  = 23). In all, 81.8% of patients in the apalutamide and 71.8% in the placebo group did not experience radiographic progression or death, and the hazard ratio for radiographic progression‐free survival favored treatment with apalutamide (hazard ratio 0.712, 95% confidence interval 0.205–2.466; P  = 0.59). At 24 months, 85.7% of patients in the apalutamide group and 81.5% in the placebo group were alive, and the hazard ratio for overall survival favored apalutamide (hazard ratio 0.840, 95% confidence interval 0.210–3.361; P  = 0.805). In the interim analysis, the median radiographic progression‐free survival and overall survival were not reached in the apalutamide group and time to cytotoxic chemotherapy was delayed following apalutamide treatment. The safety profile of apalutamide in the Japanese subpopulation was comparable with that of the global population, except for skin rash. Conclusions: The results of the present analyses suggest that apalutamide + androgen deprivation therapy in Japanese patients had favorable efficacy compared with androgen deprivation therapy alone, and these findings are comparable to those in the overall population. Apalutamide + androgen deprivation therapy can be considered as one of the therapeutic options for a broad spectrum of metastatic castration‐sensitive prostate cancer regardless of prior treatment and disease extent in Japanese patients.